Hemodialysis Patients with Cardiovascular Disease Reveal Increased Tissue Na+ Deposition - Anna-Carolina Friedrich; Peter Linz; Armin M. Nagel; Daniela Rosenhauer; Stephan Horn; Mario Schiffer; Michael Uder; Christoph Kopp; Anke Dahlmann (Kidney & Blood Pressure Research, 2021)
Background: The relationship between Na+ balance and cardiovascular disease (CVD) in hemodialysis (HD) patients is not yet fully understood. We hypothesized that HD patients co-diagnosed with CVD show increased tissue Na+ accumulation compared to HD patients without CVD. Methods: In our observational study 52 HD patients were divided into a group with (23 subjects) or without (29 subjects) a positive history of cardiovascular events. We used 23Na-Magnetic Resonance Imaging (23Na-MRI) at 3.0 Tesla to quantify Na+ content in skin and muscle of both groups directly before and after HD. Additionally, total body fluid distribution was determined by Bioimpedance Spectroscopy (BIS) and laboratory parameters were assessed. Results: Compared to HD patients without CVD, 23Na-MRI detected an increased Na+ content in skin (21.7 ± 7.3 vs. 30.2 ± 9.8 arbitrary units, a.u., p < 0.01) and muscle tissue (21.5 ± 3.6 vs 24.7 ± 6.0 a.u., p < 0.05) in patients with previous CVD events. Simultaneously measured fluid amount by BIS, including excess extracellular water (1.8 ± 1.7 vs. 2.2 ± 1.7 L, p = 0.44), was not significantly different between both groups. Tissue Na+ accumulation in HD-CVD patients was paralleled by a higher plasma concentration of the inflammation marker Interleukin-6 (5.1, IQR 5.8 vs. 8.5, IQR 7.9 pg/ml, p < 0.05). Conclusion: In our cohort, HD patients with CVD showed higher tissue Na+ content than HD patients without CVD, while no difference in body water distribution could be detected between both groups. Our findings provide evidence that the history of a cardiovascular event is associated with disturbances in tissue Na+ content in HD patients.